The value of testimonial-based beliefs in the face of AI-generated quasi-testimony - Álvarez, Felipe; Espinosa, Ruth (Aufklärung: journal of philosophy, 2024)
The value of testimony as a source of knowledge has been a subject of epistemological debates. The "trust theory of testimony" suggests that human testimony is based on an affective relationship supported by social norms. However, the advent of generative artificial intelligence challenges our understanding of genuine testimony. The concept of "quasi-testimony" seeks to characterize utterances produced by non-human entities that mimic testimony but lack certain fundamental attributes. This article analyzes these issues in depth, exploring philosophical perspectives on testimony and the implications of conversational AI technologies on our epistemic practices.